Professional English for Electrical Power Engineering. Part 2. PowerStation электронный курс - Ufa, R. A. specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences 1988- (TPU Moodle, 2022)
This course provides a foundation in Electrical and Electrical Engineering and prepares students to apply the acquired knowledge and skills in practice. Course objectives: to present a comprehensive and rigorous treatment of relay protection and automation devices in power systems. Major topics include: fundamentals of protective relays; current and voltage transformers; overcurrent, distance and differential type of protection systems; autoreclosing system and automatic switching over to a reserve source.